ANALISIS KOMPETENSI GURU KELAS V DALAM MEMPERSIAPKAN PERANGKAT PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH NEGERI 02 KOTA BENGKULU - Dewija Yanti, Anggun (Journal of Primary Education, 2023)
The purpose of this study was to determine the competence of fifth grade teachers in preparing thematic learning tools at Madrasah Ibtidaiyah Negeri 02 Bengkulu City. This research is a survey research while the method used is descriptive quantitative. Quantitative descriptive research is a research procedure that produces descriptive data in the form of written, or oral words from people and observable behavior and content analysis is a technique for gathering and analyzing the content of text, with teacher research data sources and syllabus documents and class V Thematic RPP at MIN 02 Bengkulu City. The teacher's competence in preparing learning tools is included in pedagogic competence, while the learning tools consist of (1) syllabus, (2) learning implementation plans, (3) student activity sheets, (4) student books, (5) learning media and (5) test of learning outcomes. As for the results of the RPP analysis, it is known that not all of the 17 RPPs analyzed are deficient, but in the findings there are some findings of deficiencies, namely, the existence of RPPs that do not create a complete school identity, almost all of the RPPs do not receive the authorization (signature) of teachers and principals, and there are several lesson plans that do not include attachments that contain components of learning materials, learning approaches and methods, assessment of learning outcomes and assessment formats.